Ответ:
Пошаговое объяснение:
1)
x−y=−8
z=3
10x−10y−13z
ми підставляємо x = y -8 і z = 3
10(y−8)−10y−13(3)
Давайте спростимо:
10y−80−10y−39
−80−39
−119
2)
5yz−5xz
Підставляємо x=y−8 і z = 3
5(y)(3)−5(y−8)(3)
15y−15(y−8)
15y−15y+120
120
х - у = -8
х = -8 + у
z = 3
10х - 10у - 13z = 10(-8 + y) - 10y - 13 * 3 =
-80 + 10y - 10y - 39 = -119
5yz - 5xz = 5y * 3 - 5 * (-8 + y) * 3 =
5y * 3 - 15 * (-8 + у) = 15у + 120 - 15у = 120
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Пошаговое объяснение:
1)
x−y=−8
z=3
10x−10y−13z
ми підставляємо x = y -8 і z = 3
10(y−8)−10y−13(3)
Давайте спростимо:
10y−80−10y−39
−80−39
−119
2)
5yz−5xz
Підставляємо x=y−8 і z = 3
5(y)(3)−5(y−8)(3)
15y−15(y−8)
15y−15y+120
120
Пошаговое объяснение:
х - у = -8
х = -8 + у
z = 3
1)
10х - 10у - 13z = 10(-8 + y) - 10y - 13 * 3 =
-80 + 10y - 10y - 39 = -119
2)
5yz - 5xz = 5y * 3 - 5 * (-8 + y) * 3 =
5y * 3 - 15 * (-8 + у) = 15у + 120 - 15у = 120